ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR PADA SAMSAT SURAKARTA, SRAGEN, DAN WONOGIRI - Nabuasa, Jackson Leonardo; Sugiarti, Sugiarti; Siddiq, Faiz Rahman (Jurnal Review Pendidikan dan Pengajaran, 2024)
The purpose of this study is to find out what factors influence taxpayer compliance in paying motor vehicle taxes in the cities of Surakarta, Sragen and Wonogiri. This type of research is quantitative where the population in this study uses data on taxpayer compliance in 2021 at UPPD Surakarta, Sragen and Wonogiri. The sample in this study used the slovin formula calculation and obtained 400 respondents. The results of this study conclude that the Independent Variable of Taxpayer Knowledge in SAMSAT Surakarta, Sragen and Wonogiri is not in accordance with the hypothesis where Taxpayer Knowledge has no effect on Taxpayer Compliance, the Independent Variable of Service Quality in SAMSAT Surakarta, Sragen and Wonogiri is not in accordance with the hypothesis in where Service Quality has no effect on Taxpayer Compliance, Independent Variable of Tax Sanctions in SAMSAT Surakarta, Sragen and Wonogiri is in accordance with the hypothesis where Tax Sanctions affect Taxpayer Compliance, Independent Variable Taxpayer Awareness in SAMSAT Surakarta, Sragen and Wonogiri is not in accordance with the hypothesis where Taxpayer Awareness has no effect on Taxpayer Compliance and Based on the value of the coefficient of determination, the R2 (Adjusted R Square) number is 0.956 or 95.6%, this indicates that the percentage of contribution is from the Variable Taxpayer Knowledge, Service Quality, Tax Sanctions, and Taxpayer Awareness of Taxpayer Compliance of 95.6% while the other 4.4% is influenced by other variables that are not present in this study.